Reimagining Minorities in Turkey: Before and After the AKP - Karaosmanoglu, Kerem (SETA FOUNDATION, 2010)
This article analyzes the changing concept of minority in today's Turkey. Minorities have been historically conceived as a problem by the Republican regime and a threat to the purity of the nation. For a long time, the term minority was commonly associated with the non-Muslim communities of Lausanne. Still now, non-Muslim communities are seen as passive elements in nation-centric conspiracy theories. However, the age-old definition of minority in Turkey is being challenged by a transformation on a global scale. Within this process, not only are political regimes, bureaucratic structures and nation-states being re-shaped, but social and cultural perceptions, and values and norms are also transforming. Given this context, it is insightful to focus on the AKP to understand the changing face of Turkey and vice versa. In this new setting, to what extent can the AKP, so far a reluctant reformer, satisfy the demands of non-Muslim citizens and address the problem of democracy? Turkey, it seems, is on the brink of another wave of change and the non-Muslim minorities are located at its center.
Keywords: Government & Law